Staff competencies in the planning and establishing of an institutional repository at the Botswana University of Agriculture and Natural Resources - Metlhaleng, Tlhalefo (Library and Information Studies Centre (LISC), 2019)
The study sought to ascertain staff competencies in the planning and establishing of an institutional repository at the Botswana University of Agriculture and Natural Resources (BUAN). In addressing the above objective, the study used the innovation-decision making process of the Diffusion of Innovations (DoI) theory (Rogers 1983) to formulate the following critical questions to guide the study: What knowledge, skills and personal attributes are required in the planning and establishing of a successful institutional repository in an academic institution?; Do BUAN staff (academics and relevant support staff) have the knowledge, skills and personal attributes necessary for planning and establishing a successful repository?; How significant a role do personal attributes such as attitudes and perceptions play in the planning and establishing of an IR at BUAN?; and, What measures may be put in place to reinforce the planning and establishing of an institutional repository at the BUAN Library? The research paradigm suitable for this study was the pragmatic paradigm because of diverse types of data used in the study. The study employed a convergent parallel mixed methods design by using both quantitative and qualitative research methods to collect data concurrently. It adopted a case study approach as the researcher undertook an in-depth enquiry into staff competencies in the planning and establishing of an institutional repository at BUAN. The study population consisted of 201 BUAN academics, three Library repository staff, and two Information Technology (IT) staff. Semi-structured interviews were used to source data from purposively selected library repository staff and BUAN IT staff. A structured questionnaire was administered to the academics. Descriptive statistics was used in the analysis of the study’s quantitative data and thematic content analysis for its qualitative data. A number of knowledge sets, skills and personal attributes emerged from the study as being required in the planning and establishing of a successful repository at BUAN, critical amongst these being knowledge of metadata and metadata standards. An important recommendation emanating from the study related to repository advocacy and outreach among BUAN academics as well as on-going training of library repository staff to keep them abreast of latest repository developments.